Kemampuan Siswa Dalam Membaca Al-Qur’an secara Tartil - Neneng Ayu Indra Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Reading the Qur'an in tartil is an advanced skill that needs to be prepared as early as possible, including for elementary school-aged children. However, tartil reading of the Qur'an for elementary school students often does not get the attention it deserves. Therefore, the purpose of the study was to determine the tartil reading ability of the 4th graders at SDIT Ar-Rahman Motik, South Jakarta. This study uses a qualitative descriptive study by conducting experiments on 4th grade students of SDIT Ar-Rahman Motik. The research subjects were 4th grade students at SDIT Ar-Rahman Motik, South Jakarta. The results showed that the 4th grade students of SDIT Ar-rahman Motik were mostly able to improve their reading of the Qur'an in tartil. Reading the Qur'an in tartil is very effective in improving the reading skills of the 4th graders at SDIT Ar-Rahman Motik, South Jakarta. Keywords: Reading the Qur'an, Tartil, elementary school.